Unleashing the Potential of Different Method of Paddy Straw Substrate Bag for Enhanced Yield and Biological Efficiency of Milky Mushroom - Marimuthu Elangovan; Vaithiyalingam Gopinath; Manikandan Karuppiah; Mohan Kumar Biswas (Archives of Current Research International, 2024)
Mushrooms, particularly Calocybe indica, are highly regarded for their distinctive flavour and numerous health benefits. This study investigates various method of paddy straw substrate bags: rolled paddy straw, intact paddy straw, and chopped paddy straw to optimize the cultivation of C. indica. Employing a Completely Randomized Design (CRD), we analysed growth parameters, yield, and biological efficiency of mushrooms cultivated on these substrates. The results indicated that chopped paddy straw was the most effective substrate, significantly reducing the time for spawn run to 14.20 days, pinhead formation to 11.80 days, and sporophore maturation to 10.20 days. This method yielded the highest overall production at 664.50 g, along with a biological efficiency of 66.45%. In contrast, intact paddy straw exhibited moderate growth performance, while rolled paddy straw resulted in the lowest yield at 451.30 g and took the longest time for all growth stages, which may be attributed to less compactness in the substrate beds. The number of sporophores produced also varied, with chopped paddy straw yielding an average of 10.6 sporophores, compared to 8.6 from intact paddy straw and 7.2 from rolled paddy straw. Although stipe length and pileus diameter showed non-significant differences among treatments, they did not contribute meaningfully to yield or biological efficiency. Overall, the findings highlight that chopped paddy straw is the most suitable substrate preparation method for cultivating C. indica, enhancing both yield and efficiency in production. This research contributes valuable insights for mushroom cultivation practices, particularly in tropical regions where high temperatures prevail.